Gradient pore cathode catalyst layer membrane electrode and preparation method thereof
By using high water-soluble polymers of different molecular weights to construct a cathode catalytic layer with gradient pore structure in fuel cell membrane electrodes, the problems of high platinum load and single pore structure are solved, and the effects of reducing oxygen transmission resistance and improving battery performance are achieved.
Patent Information
- Application Number
- CN202411394046.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
The high loading of platinum in existing fuel cell membrane electrodes leads to high costs. The single pore structure of the traditional catalytic layer cannot meet the transmission needs of oxygen and water, and pore-forming agents are difficult to produce on a large scale.
Highly water-soluble polymers with different molecular weights are used as pore-forming agents, and a cathodic catalytic layer with gradient pore structure is constructed on the proton exchange membrane and the gas diffusion layer through CCM and GDE technologies to reduce the oxygen transmission resistance.
It effectively reduces the oxygen transmission resistance of the membrane electrode, improves the performance of the fuel cell, meets the differential requirements of gas and water transmission, and simplifies the removal process of pore-forming agents.
Smart Images

Figure CN119252942A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a gradient pore cathode catalyst layer membrane electrode and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells have attracted widespread attention as the most promising alternative to internal combustion engines due to their unique advantages such as high power density, high efficiency and zero emissions. However, the kinetic rate of the oxygen reduction reaction in the cathode of fuel cells is slow, and a large amount of platinum-based catalysts must be used to achieve the desired output power. The large-scale use of platinum has led to high costs for membrane electrodes in fuel cells. The cost of platinum in the membrane electrode alone accounts for more than 41% of the cost of the fuel cell stack. The high cost is the main obstacle to the large-scale commercialization of fuel cells in the future. Therefore, reducing the platinum loading of the membrane electrode and reducing production costs is the only way to achieve the application of fuel cells.
[0003] For fuel cell membrane electrode, when the platinum loading is reduced to 0.2 mgPt / cm 2 When the oxygen transport resistance in the cathode catalyst layer accounts for the largest part of the total transport resistance and dominates the performance of the fuel cell. Reasonable design and regulation of the pore structure of the catalyst layer to reduce the oxygen transport resistance and increase the number of three-phase interfaces are the key to improving the performance of low-platinum membrane electrodes. However, the traditional strategy for regulating the pore structure of the catalyst layer is to directly coat a slurry containing platinum carbon, ionomer, solvent and pore former (ammonium salt or oxide) on the substrate to form a single catalyst layer. Although this strategy can improve the pore structure of the catalyst layer, the pore size and porosity parameters of the entire catalyst layer are relatively single. In the actual operation of the membrane electrode, there are obvious differences in the diffusion length, diffusion rate and concentration of O2 / H2O in the vertical direction of the catalyst layer. The catalyst layer with a single pore distribution cannot meet the transmission requirements of gas and water at the same time, which often leads to "flooding" and gas mass transfer problems in the working process of the battery. In addition, the pore formers selected by the currently reported methods are mostly ammonium salts or oxides, which are difficult to achieve in the actual preparation of slurry and membrane power production. Therefore, it is necessary to select a type of pore-forming agent that is easy to mass-produce to construct a catalytic layer structure with a gradient distribution of pores from the proton exchange membrane side to the diffusion layer side, so as to optimize the transmission of substances to the greatest extent, reduce the oxygen transmission resistance, and improve the performance of the fuel cell.
[0004] The invention patent with the authorization announcement number CN1259744C discloses a method for regulating the pore structure of the catalyst layer of a proton exchange membrane, by introducing a pore-forming agent of NH4HCO3 with a low decomposition temperature into the slurry, and the pore-forming agent decomposes during the drying process of the slurry to increase the porosity of the catalyst layer. However, the patent focuses on proposing a new pore-forming agent to increase the porosity of the catalyst layer, and does not involve the design of the gradient pore of the catalyst layer. Moreover, the addition of large particles of NH4HCO3 makes the particle size of the prepared catalyst slurry too large, making the slurry difficult to disperse; the introduction of ammonium ions easily combines with the sulfonate group of the perfluorosulfonic acid side chain, reducing the proton conduction of the ionomer.
[0005] The invention patent with application publication number CN117497776A discloses a method for preparing a porous catalyst layer membrane electrode. The strategy is to use nano-scale oxides (CuO, ZnO and MgO) as pore-forming agents. After coating the catalyst layer, it is difficult to remove the oxides. The oxides must be removed by washing with sulfuric acid to form pores in the catalyst layer. However, in actual production, the use of strong acid not only adds to the production process but also increases the safety risks of production, which is not conducive to large-scale membrane electrode production. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a gradient pore cathode catalyst layer membrane electrode and a preparation method thereof. The purpose of the present invention is to use highly water-soluble polymers of different molecular weights as pore-forming agents to adjust the pore structure of the inner and outer catalyst layers, construct a gradient pore catalyst layer, thereby reducing the oxygen transmission resistance of the membrane electrode and improving battery performance.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:
[0008] In a first aspect, an embodiment of the present invention provides a method for preparing a gradient pore cathode catalyst layer membrane electrode, comprising the following steps:
[0009] Step S1, preparation of pore-forming agent solution: adding a perfluorosulfonic acid resin solution to a water-alcohol mixed solvent, stirring thoroughly, and testing the viscosity using a rheometer. When the viscosity no longer changes, the perfluorosulfonic acid resin solution is matured, and a low molecular weight pore-forming agent and a high molecular weight pore-forming agent are added to the matured resin solution, respectively, and mixed to form pore-forming agent solutions with different molecular weights;
[0010] Step S2, preparation of cathode gradient catalytic layer: ultrasonically mixing the platinum carbon catalyst and the low molecular weight pore-forming agent solution prepared in step S1 to prepare the inner catalytic layer slurry, coating the cathode side of the proton exchange membrane, and drying to form the cathode inner catalytic layer;
[0011] The outer catalyst layer slurry prepared by ultrasonically mixing the platinum-carbon catalyst and the high molecular weight pore-forming agent solution prepared in step S1 is coated on the gas diffusion layer side and dried to form the cathode outer catalyst layer;
[0012] Step S3, preparation of cathode gradient pore membrane electrode: encapsulating the proton exchange membrane coated with the cathode inner catalyst layer and the anode catalyst layer with a frame, and then pasting the gas diffusion layer coated with the cathode outer catalyst layer and the anode gas diffusion layer on the surface respectively, and preparing the membrane electrode after hot pressing according to the target parameters under a hot press;
[0013] Step S4, pore-forming agent removal: The membrane electrode is mounted on a test fixture and activated with constant current loading at a battery temperature of 60-85°C and a humidity of 50-100%. When the battery voltage is 0.4-0.6V, the corresponding current density is maintained for 2-20h to complete the removal of the pore-forming agent.
[0014] The cathode and anode gas diffusion layers are selected from one or more of TGL-R-045, TGL-R-055, TGL-R-060, TGL-R-090 and TGL-R-120 produced by Toray of Japan.
[0015] Furthermore, in step S1, the low molecular weight pore former and the high molecular weight pore former are both highly water-soluble polymers, and are selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyacrylic acid, and polyethylene oxide;
[0016] The molecular weight of the low molecular weight pore former is 200-600, and its mass is 0.01-0.3 of the mass of the catalyst; the molecular weight of the high molecular weight pore former is 800-1200, and its mass is 0.01-0.2 of the mass of the catalyst.
[0017] It is particularly noted that in the preparation of the pore-forming agent solution, the perfluorosulfonic acid resin solution and the water-alcohol solution must first be mixed and matured, mainly to fully transform the morphology of the main and side chains of the resin. The dispersed morphology of the main and side chains of the perfluorosulfonic acid resin is different in solutions with different dielectric constants. When directly added in the order of catalyst-water-alcohol solvent-resin solution, the solvent environment in which the resin is located changes dramatically due to the addition of the water-alcohol solution, and the resin morphology changes accordingly at this time. However, due to the strong adsorption of the resin and carbon, the resin morphology fails to fully transform and is adsorbed on the carbon, which ultimately leads to uneven coating of the resin on the carbon and reduces performance. Therefore, it is necessary to first mix the resin stock solution and water-alcohol and then prepare the matured resin solution after the resin morphology is fully transformed. Considering that the carbon carrier in the catalyst itself will strongly adsorb to the resin, if the catalyst-matured perfluorosulfonic acid resin solution-pore-forming agent is mixed in this order, the pore-forming agent is difficult to interact with the resin chain, and the pore-forming effect is not good. Therefore, the matured resin solution is mixed with the polymer of the aqueous solution, and the pore-forming agent solution is formed by cross-linking the non-polar main chain of the resin and the polymer. Finally, a dense catalytic layer is formed through coating, and the battery is subsequently activated under high humidity and high current density conditions. At this time, the battery produces a large amount of water, and the polymer is particularly water-soluble, so it is dissolved and discharged in the water generated at the cathode, thereby forming pores in the originally densely coated resin layer.
[0018] Furthermore, in step S1, when the perfluorosulfonic acid resin solution is matured, the mass ratio of water to alcohol in the water-alcohol mixed solvent is 1:10-10:1, and the stirring time of the maturation process is 2-48h;
[0019] The water-alcohol mixed solvent is a mixed solution of water and one or more reagents selected from ethanol, isopropanol, n-propanol, n-butanol, ethylene glycol and propylene glycol.
[0020] The perfluorosulfonic acid resin solution is a mixed solution of one or more resins selected from D520 and D2020 produced by DuPont or D79 and D72 produced by Solvay.
[0021] Furthermore, in step S2, the cathode inner catalyst layer adopts CCM technology, and the inner catalyst layer slurry is directly coated on the proton exchange membrane, and the platinum loading of the inner catalyst layer is 0.1-0.3 mg / cm 2 ;
[0022] The cathode outer catalyst layer adopts GDE technology to directly coat the outer catalyst layer slurry on the gas diffusion layer. The platinum loading of the outer catalyst layer is 0.05-0.2 mg / cm 2 .
[0023] Furthermore, in step S2, the platinum-carbon catalyst used in the cathode inner and outer catalyst layer slurries is a high specific surface area carbon-supported platinum catalyst, and the specific surface area of the carbon carrier is 500-1000m 2 / g, platinum content is 10-70wt%;
[0024] The platinum-carbon catalyst used in the anode catalyst layer slurry is a low specific surface area carbon-supported platinum catalyst, and the specific surface area of the carbon carrier is 50-200m 2 / g, and the platinum content is 20-60wt%.
[0025] Furthermore, in step S3, the hot pressing conditions are one of the following: temperature of 80-120°C, hot pressing pressure of 50-100 kgf / cm 2 Under the conditions of heat pressing for 20-30min;
[0026] Temperature 120-160℃, hot pressing pressure 30-50kgf / cm 2 , hot pressing time 10-20min;
[0027] Or temperature 160-180℃, hot pressing pressure 10-30kgf / cm 2 , hot pressing time 1-10min.
[0028] Furthermore, in the inner catalyst layer slurry, the outer catalyst layer slurry and the anode catalyst layer slurry, the total mass of the catalyst and the perfluorosulfonic acid resin is 0.5wt%-20wt% of the slurry, and the mass ratio of the perfluorosulfonic acid resin to the catalyst is 1:4-4:1.
[0029] Furthermore, in step S3, the drying conditions of the catalyst layer are: drying at a temperature of 20-60°C for 15-30 minutes; or drying at a temperature of 60-100°C for 1-15 minutes.
[0030] Furthermore, in step S3, the cathode outer catalyst layer on the cathode gas diffusion layer in the membrane electrode is bonded to the cathode inner catalyst layer on the proton exchange membrane;
[0031] When preparing the anode catalyst layer, a platinum-carbon catalyst, a perfluorosulfonic acid resin and a solvent are mixed to prepare an anode catalyst layer slurry, which is then coated on the anode side of the proton exchange membrane and dried to form the anode catalyst layer.
[0032] In the second aspect, an embodiment of the present invention provides a gradient pore cathode catalyst layer membrane electrode, which is prepared by the preparation method described in the first aspect. The membrane electrode is used to prepare a low-temperature proton exchange membrane fuel cell, and the operating temperature of the low-temperature proton exchange membrane fuel cell is less than 100°C.
[0033] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0034] 1. The present invention combines the traditional GDE (catalyst coated gas diffusion layer) and CCM (catalyst coated proton exchange membrane) technologies, and coats a low molecular weight water-soluble polymer pore-forming agent on the proton exchange membrane to form an inner cathode catalyst layer with smaller pores; and coats a high molecular weight water-soluble polymer pore-forming agent on the gas diffusion layer to form an outer cathode catalyst layer with larger pores. Finally, a catalyst layer with a gradient distribution of inner and outer pores is obtained by hot pressing, which can not only effectively reduce the contact resistance between different interfaces, but also the gradient pore structure can effectively meet the differentiated requirements of gas and water transport in fuel cells.
[0035] 2. The current method for regulating the pore size structure of the catalyst layer only uses a single pore former, and the pores and pore size distribution range formed are narrow, and the traditional pore former brings additional dispersion and production difficulties. The present invention uses a water-soluble polymer pore former, selects polymers of different molecular weights to construct pores of different sizes in the inner and outer catalyst layers, expands the pore distribution gradient, and the water-soluble pore former can be removed through the generated water during battery activation, without adverse effects on the membrane electrode.
[0036] 3. The membrane electrode with gradient pore structure designed in the present invention can not only be used in proton exchange membrane fuel cells, but also has certain reference significance for the regulation of catalyst layer structure of proton exchange membrane electrolyzer and anion exchange membrane electrolyzer. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the structure of the gradient pore cathode catalyst layer membrane electrode in an embodiment of the present invention.
[0038] Figure 2 This is a flow chart for preparing the cathode gradient pore structure catalyst layer in an embodiment of the present invention.
[0039] Figure 3 Graph showing polarization curves of membrane electrodes in Example 1, Comparative Example 1 and Comparative Example 2.
[0040] Figure 4 Graph showing polarization curves of membrane electrodes in Example 1, Example 2 and Example 3.
[0041] Figure 5 Graph showing the polarization curves of the membrane electrodes in Comparative Examples 1, 2 and 3.
[0042] Figure 6 Graphs showing polarization curves of membrane electrodes in Example 1, Comparative Example 4, Comparative Example 5 and Comparative Example 6.
[0043] Explanation of the reference numerals: 1 - cathode gas diffusion layer; 2 - cathode outer catalyst layer; 3 - cathode inner catalyst layer; 4 - proton exchange membrane; 5 - anode catalyst layer; 6 - anode gas diffusion layer. DETAILED DESCRIPTION
[0044] like Figure 1 As shown, a gradient pore cathode catalyst layer membrane electrode comprises, from top to bottom, a cathode gas diffusion layer 1, a cathode outer catalyst layer 2, a cathode inner catalyst layer 3, a proton exchange membrane 4, an anode catalyst layer 5 and an anode gas diffusion layer 6. The membrane electrode is mainly used to prepare a low-temperature proton exchange membrane fuel cell. The operating temperature of the fuel cell is less than 100°C. The proton exchange membrane adopts a perfluorosulfonic acid resin membrane. The cathode inner catalyst layer 3 adopts a low molecular weight pore former to form small pores, and the cathode outer catalyst layer 2 adopts a high molecular weight pore former to form large pores.
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] Example 1
[0047] A method for preparing a cathode gradient pore membrane electrode, such as Figure 2 As shown, the following steps are included:
[0048] Step S1, preparation of pore-forming agent solution: adding DuPont D2020 perfluorosulfonic acid resin stock solution to a mixed solvent of water and n-propanol, heating to 60°C and stirring thoroughly, testing the viscosity with a rheometer, and when the viscosity does not change, the resin solution is matured, and then low molecular weight (polyethylene glycol, molecular weight 200) and high molecular weight (polyethylene glycol, molecular weight 1000) pore-forming agents are added respectively, and mixed to prepare pore-forming agent solutions with different molecular weights;
[0049] Step S2, preparation of cathode inner catalytic layer (CCM method): 50wt% Pt / C catalyst and low molecular weight pore former solution (polyethylene glycol, molecular weight 200) were mixed, and a catalyst slurry was prepared after homogenization and degassing, wherein the solid content of the slurry was 12wt%, the mass ratio of water to n-propanol was 1:1, the mass ratio of perfluorosulfonic acid resin to Pt / C catalyst was 1:2, and the mass ratio of pore former to perfluorosulfonic acid resin was 1:20. The prepared catalyst slurry was coated on the cathode side of the proton exchange membrane and dried at 80°C for 10min to form a platinum loading of 0.10mg / cm 2 The cathode inner catalytic layer;
[0050] Step S3, preparation of cathode outer catalytic layer (GDE method): 50wt% Pt / C catalyst and high molecular weight pore former solution (polyethylene glycol, molecular weight 1000) were mixed, and a catalyst slurry was prepared after homogenization and degassing, wherein the solid content of the slurry was 12wt%, the mass ratio of water to n-propanol was 1:1, the mass ratio of perfluorosulfonic acid resin to Pt / C catalyst was 1:2, and the mass ratio of pore former to perfluorosulfonic acid resin was 1:20. The prepared catalyst slurry was coated on the microporous layer side of the Toray TGL-R-090 gas diffusion layer and dried at 80°C for 10min to form a platinum loading of 0.10mg / cm 2 The cathode outer catalytic layer;
[0051] The catalysts in the cathode inner catalyst layer and the cathode outer catalyst layer are both TANAKA platinum carbon catalysts with model TEC10E50E;
[0052] Step S4, preparation of anode catalyst layer (CCM method): 50wt% Pt / C catalyst and matured perfluorosulfonic acid resin solution are mixed, and a uniform catalyst slurry is prepared after homogenization and degassing, wherein the solid content of the slurry is 8wt%, the mass ratio of water to n-propanol is 1:1, and the mass ratio of perfluorosulfonic acid resin to Pt / C catalyst is 1:2. The prepared catalyst slurry is coated on the anode side of the proton exchange membrane in step S2, and dried at 80°C for 10min to form a platinum loading of 0.10mg / cm 2 Anode catalyst layer;
[0053] The catalyst in the anode catalyst layer is a TANAKA platinum-carbon catalyst of model TEC10EA50E.
[0054] Step S5, membrane electrode packaging: the proton exchange membrane coated with the anode catalyst layer and the cathode inner catalyst layer is packaged with a PEN frame, and the diffusion layer containing the cathode outer catalyst layer and the pure anode diffusion layer are attached to the anode and cathode sides respectively, and hot-pressed in a hot press according to the target parameters (temperature: 120°C, pressure: 30kgf / cm 2 , time: 10min) to prepare an area of 25cm 2 The membrane electrode is used for electrochemical testing;
[0055] Step S6, pore-forming agent removal: The membrane electrode was mounted on a test fixture and activated with constant current loading at a battery temperature of 80° C. and a humidity of 100%. When the battery voltage was 0.4 V, the corresponding current density was maintained for 6 h to complete the removal of the pore-forming agent.
[0056] Example 2
[0057] This embodiment is basically the same as Embodiment 1, except that when preparing the cathode gradient catalytic layer, the CCM method is used to prepare the gradient catalytic layer, that is, the cathode inner catalytic layer slurry (containing a low molecular weight pore-forming agent) is first coated on the proton exchange membrane, and the cathode inner catalytic layer is formed after drying; and the cathode outer catalytic layer slurry (containing a high molecular weight pore-forming agent) is then coated on the surface of the cathode inner catalytic layer, and the cathode outer catalytic layer is formed after drying, thereby finally obtaining the gradient catalytic layer.
[0058] Example 3
[0059] This embodiment is basically the same as Embodiment 1, except that when preparing the cathode gradient catalytic layer, the GDE method is used to prepare the gradient catalytic layer, that is, the cathode outer catalytic layer slurry (containing a high molecular weight pore-forming agent) is first coated on the cathode gas diffusion layer, and then the cathode outer catalytic layer is formed after drying; and then the cathode inner catalytic layer slurry (containing a low molecular weight pore-forming agent) is coated on the surface of the cathode outer catalytic layer, and then the cathode inner catalytic layer is formed after drying, and finally the gradient catalytic layer is obtained.
[0060] Comparative Example 1
[0061] This comparative example is basically the same as Example 1, both using CCM method to prepare the inner catalyst layer and GDE method to prepare the outer catalyst layer, except that low molecular weight (polyethylene glycol, molecular weight 200) pore-forming agent is used to prepare the cathode catalyst layer in both the inner and outer catalyst layers.
[0062] Comparative Example 2
[0063] This comparative example is basically the same as Example 1, both adopt CCM method to prepare the inner catalytic layer and GDE method to prepare the outer catalytic layer, except that high molecular weight (polyethylene glycol, molecular weight 1000) pore-forming agent is used in both the inner and outer catalytic layers.
[0064] Comparative Example 3
[0065] This comparative example is basically the same as Example 1, both of which adopt the CCM+GDE method to prepare the catalyst layer, except that the slurry does not contain any pore-forming agent when preparing the catalyst layer.
[0066] Comparative Example 4
[0067] This comparative example is basically the same as Example 1, except that the activation time is 2 hours when the pore-forming agent is removed.
[0068] Comparative Example 5
[0069] This comparative example is basically the same as Example 1, except that the activation time is 4 hours when the pore-forming agent is removed.
[0070] Comparative Example 6
[0071] This comparative example is basically the same as Example 1, except that the activation time is 8 hours when the pore-forming agent is removed.
[0072] First, the resin solution was aged before the pore-forming agent solvent was prepared. As shown in Table 1, the viscosity of the resin solution increased sharply after the addition of the water-alcohol solution, indicating that the main chain and side chain morphology had undergone a sudden change. As the aging progressed, the viscosity gradually decreased and stabilized, and the aging process of the resin solution was finally completed. Water-soluble pore-forming agents of different molecular weights were added to the aged resin solution to prepare a pore-forming agent solution. Different membrane electrodes were prepared according to the conditions shown in Table 2 for testing and analysis.
[0073] Table 1 Viscosity of perfluorosulfonic acid resin liquid during aging
[0074] Ripening time <![CDATA[Viscosity (cP) @ 40 s -1 > Resin stock solution 202.17 Add water-alcohol mixed solvent and mature for 0h 360.32 Add water-alcohol mixed solvent and mature for 4 hours 280.67 Add water-alcohol mixed solvent and mature for 8h 265.19 Add water-alcohol mixed solvent and ripen for 12 hours 261.25 Add water-alcohol mixed solvent and mature for 24 hours 262.62
[0075] Table 2 Summary of experimental conditions for examples and comparative examples
[0076]
[0077]
[0078] Figure 5 The polarization curves of the membrane electrodes prepared in Comparative Examples 1, 2 and 3 are shown in Figure 1. It can be seen from the figure that the performance of the three membrane electrodes is basically similar at low current density, while at high current density (>1.5A / cm 2 ) performance difference gradually becomes obvious. The original catalyst layer has low porosity and small pore size, the mass transfer resistance of the membrane electrode (Comparative Example 3) is large, and the mass transfer polarization is obvious under high current. After the pore-forming agent is used to expand the pores, the mass transfer resistance of the membrane electrode (Comparative Examples 1 and 2) is reduced, showing improved performance under high current density. Further, as Figure 3 As shown, when a gradient catalytic layer is prepared using polymers of different molecular weights (Example 1), the performance is further improved compared with a membrane electrode using a single molecular weight polymer (Comparative Examples 1 and 2). This is mainly because, when a catalytic layer is prepared using a polymer of a single molecular weight, although the pores can be enlarged and oxygen mass transfer can be promoted, the pore distribution of the catalytic layer prepared by this method is relatively single, and there is no obvious difference in the porosity of the inner and outer catalytic layers, which does not meet the different requirements for water vapor transmission on the membrane electrode near the membrane side and the near diffusion layer side in actual working conditions. The use of polymers of different molecular weights to prepare a gradient catalytic layer can better meet the needs of the membrane electrode for gas and water mass transfer at work. Specifically, a high molecular weight polymer is introduced near the gas diffusion layer side to construct a high porosity, large pore outer catalytic layer, which can promote the discharge of water and the introduction of gas; a low molecular weight polymer is introduced near the proton exchange membrane side to construct a low porosity, small pore inner catalytic layer, which is conducive to good contact between the proton exchange membrane and the catalytic layer and effective wetting of the membrane, reducing contact resistance and improving proton conduction.
[0079] In addition, considering the different preparation processes of membrane electrodes, we compared the membrane electrode performance of gradient pore catalytic layers prepared by CCM and GDE in detail. Figure 4 The polarization curve results show that the gradient catalyst layer prepared by combining CCM and GDE has the best performance. It is difficult for a single CCM or GDE method to take into account the contact resistance between the proton exchange membrane and the catalyst layer or the gas diffusion layer and the catalyst layer. The above results fully demonstrate that the preparation method of combining CCM and GDE to construct a cathode catalyst layer with different pore structures in the inner and outer catalyst layers can minimize the oxygen transfer resistance of the membrane electrode, inhibit mass transfer polarization losses, and improve the performance of the battery at high current density.
[0080] In order to further explore whether the pore-forming agent can be removed during the battery activation process, additional membrane electrodes with different activation times (2h, 4h, 6h and 8h) were prepared for analysis. Figure 6 It can be clearly seen from the results that the electrode performance with activation time of 2h and 4h is very poor, and the internal resistance of the battery is high, while when the activation time reaches 6h and 8h, the performance is basically the same, and the internal resistance is not much different. The internal resistance of the membrane electrode mainly includes the proton conduction resistance of the proton exchange membrane, the proton and electron conduction resistance in the catalyst layer, and the contact resistance of each interface. Since the same process and materials are used, the main difference in internal resistance lies in the proton and electron conduction resistance in the catalyst layer. The polymer polyethylene glycol itself has large electronic and proton resistance. If it is not removed, the internal resistance of the battery will be high and the battery performance will be reduced. Therefore, the change in the internal resistance of the battery at different activation times can represent the amount of polymer residue. Combined with the data in Table 3, the water-soluble polymer in the battery is basically removed when it is activated for more than 6h, and the battery performance is the best.
[0081] Table 3 Performance and internal resistance of membrane electrode at different activation times
[0082] Compare Projects Activation time (h) <![CDATA[Voltage (V @ 2 A / cm 2 )]]> <![CDATA[Area internal resistance (mΩ·cm 2 @ 2 A / cm 2 )]]> Comparative Example 4 2 0.615 57.50 Comparative Example 5 4 0.680 43.21 Example 1 6 0.705 40.07 Comparative Example 6 8 0.708 39.82
[0083] The embodiment of the present invention uses a highly water-soluble polymer as a pore-forming agent to prepare a double-layer gradient cathode catalyst layer membrane electrode, which mainly uses highly water-soluble pore-forming agents of different molecular weights to prepare cathode inner and outer catalyst layers with different pore structures on the proton exchange membrane and the gas diffusion layer, and finally obtains a gradient pore catalyst layer membrane electrode by hot pressing. Compared with the traditional catalyst layer preparation method, the pore-forming agent is easy to remove and facilitates actual slurry dispersion and production. The constructed gradient cathode catalyst layer contains two inner and outer catalyst layers with different pore sizes. The inner catalyst layer with low pores and small pores close to the proton exchange membrane side ensures good contact between the proton exchange membrane and the catalyst layer and effective wetting of the membrane, thereby improving proton conduction. The outer catalyst layer with high pores and large pores close to the gas diffusion layer side ensures the removal of water and the introduction of gas. This gradient pore cathode catalyst layer can effectively reduce the flooding and gas mass transfer problems during the operation of the membrane electrode, and improve the performance of the battery under high current density conditions.
[0084] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a gradient pore cathode catalyst layer membrane electrode, characterized in that: The following steps are involved: Step S1, preparation of pore-forming agent solution: adding a perfluorosulfonic acid resin solution to a water-alcohol mixed solvent, stirring thoroughly, and when the viscosity no longer changes, completing the aging of the perfluorosulfonic acid resin solution, respectively adding a low molecular weight pore-forming agent and a high molecular weight pore-forming agent to the aging resin solution, and mixing to form pore-forming agent solutions with different molecular weights; Step S2, preparation of cathode gradient catalytic layer: ultrasonically mixing the platinum carbon catalyst and the low molecular weight pore-forming agent solution prepared in step S1 to prepare the inner catalytic layer slurry, coating the cathode side of the proton exchange membrane, and drying to form the cathode inner catalytic layer; The outer catalyst layer slurry prepared by ultrasonically mixing the platinum-carbon catalyst and the high molecular weight pore-forming agent solution prepared in step S1 is coated on the gas diffusion layer side and dried to form the cathode outer catalyst layer; Step S3, preparation of cathode gradient pore membrane electrode: encapsulating the proton exchange membrane coated with the cathode inner catalyst layer and the anode catalyst layer with a frame, and then pasting the gas diffusion layer coated with the cathode outer catalyst layer and the anode gas diffusion layer on the surface respectively, and preparing the membrane electrode after hot pressing according to the target parameters under a hot press; Step S4, pore-forming agent removal: The membrane electrode is mounted on a test fixture and activated with constant current loading at a battery temperature of 60-85°C and a humidity of 50-100%. When the battery voltage is 0.4-0.6V, the corresponding current density is maintained for 2-20 h to complete the removal of the pore-forming agent.
2. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S1, the low molecular weight pore former and the high molecular weight pore former are both highly water-soluble polymers, and are selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyacrylic acid, and polyethylene oxide; The molecular weight of the low molecular weight pore former is 200-600, and its mass is 0.01-0.3 of the mass of the catalyst; the molecular weight of the high molecular weight pore former is 800-1200, and its mass is 0.01-0.2 of the mass of the catalyst.
3. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S1, when the perfluorosulfonic acid resin solution is matured, the mass ratio of water to alcohol in the water-alcohol mixed solvent is 1:10-10:1, and the stirring time of the maturation process is 2-48 h; The water-alcohol mixed solvent is a mixed solution of water and one or more of ethanol, isopropanol, n-propanol, n-butanol, ethylene glycol and propylene glycol.
4. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S2, the cathode inner catalyst layer adopts CCM technology, and the inner catalyst layer slurry is directly coated on the proton exchange membrane, and the platinum loading of the inner catalyst layer is 0.1-0.3 mg / cm 2 ; The cathode outer catalyst layer adopts GDE technology to directly coat the outer catalyst layer slurry on the gas diffusion layer. The platinum loading of the outer catalyst layer is 0.05-0.2 mg / cm 2 .
5. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S2, the platinum-carbon catalyst used in the cathode inner and outer catalyst layer slurries is a high specific surface area carbon-supported platinum catalyst, and the specific surface area of the carbon carrier is 500-1000 m 2 / g, platinum content is 10-70 wt%; In step S3, the platinum-carbon catalyst used in the anode catalyst layer slurry is a low specific surface area carbon-supported platinum catalyst, and the specific surface area of the carbon carrier is 50-200 m 2 / g, and the platinum content is 20-60 wt%.
6. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S3, the hot pressing conditions are one of the following: temperature of 80-120°C, hot pressing pressure of 50-100 kgf / cm 2 Under the conditions of heat pressing for 20-30 min; Temperature 120-160 ℃, hot pressing pressure 30-50 kgf / cm 2 , hot pressing time 10-20 min; Or temperature 160-180 ℃, hot pressing pressure 10-30 kgf / cm 2 , hot pressing time 1-10 min.
7. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In the inner catalyst layer slurry, the outer catalyst layer slurry and the anode catalyst layer slurry, the total mass of the catalyst and the perfluorosulfonic acid resin is 0.5 wt%-20 wt% of the slurry, and the mass ratio of the perfluorosulfonic acid resin to the catalyst is 1:4-4:
1.
8. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S3, the drying conditions of the catalyst layer are: drying at a temperature of 20-60° C. for 15-30 min; or drying at a temperature of 60-100° C. for 1-15 min.
9. The method for preparing a gradient pore cathode catalyst layer membrane electrode according to claim 1, characterized in that: In step S3, the cathode outer catalyst layer on the cathode gas diffusion layer in the membrane electrode is bonded to the cathode inner catalyst layer on the proton exchange membrane; When preparing the anode catalyst layer, a platinum-carbon catalyst, a perfluorosulfonic acid resin and a solvent are mixed to prepare an anode catalyst layer slurry, which is then coated on the anode side of the proton exchange membrane and dried to form the anode catalyst layer.
10. A gradient pore cathode catalyst layer membrane electrode, characterized in that: The membrane electrode is prepared by the preparation method according to any one of claims 1 to 9, and is used to prepare a low-temperature proton exchange membrane fuel cell, wherein the operating temperature of the low-temperature proton exchange membrane fuel cell is less than 100°C.
Citation Information
Cited By
Method for measuring oxygen transmission resistance in pores of porous carbon carrier in porous carbon-supported platinum catalyst of catalyst layer of proton exchange membrane fuel cell
CN120558807A
Cathode catalyst layer and preparation method thereof, membrane electrode and fuel cell
CN120809840A
Cathode catalytic layer, preparation method thereof, membrane electrode and fuel cell
CN120809840B
Fuel cell catalyst layer and preparation method and application thereof
CN121260811A
